2010
DOI: 10.1021/ol1025525
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of 7-Substituted Purines via 7,8-Dihydropurines

Abstract: A simple and efficient protocol for the preparation of 7-substituted purines is described. 6- and 2,6-Dihalopurines were N(9)-tritylated and then transformed to 7,8-dihydropurines by DIBAL-H. Subsequent N(7)-alkylation followed by N(9)-trityl deprotection with trifluoroacetic acid was accompanied by spontaneous reoxidation, which led to the 7-substituted purines at 55-88% overall isolated yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Yield 242 mg (28 %), yellow oil. The spectroscopic data were in good agreement with those reported before 28…”
Section: Methodssupporting
confidence: 91%
“…Yield 242 mg (28 %), yellow oil. The spectroscopic data were in good agreement with those reported before 28…”
Section: Methodssupporting
confidence: 91%
“…The syntheses of compounds 1–4 and 6–7 have been described previously . For the selective preparation of 7‐substituted purines, an alternative synthetic approach could be used . The preparation of compounds 5 , 9 and 10 will be described in a separate paper with the description of their biological activities.…”
Section: Methodsmentioning
confidence: 99%
“…9 Recently, as a part of our ongoing project to develop a new selective synthesis of C-and N 7 -substituted pu-rines, 9,10 we have developed a new practical route to the synthesis of N 7 -alkyl-6-halo and N 7 -alkyl-2,6-dihalopurines based on the reaction of 9-tritylated-7,8-dihydropurines with alkyl halide in the presence of a base. 11 One complication of the reported procedure is that the solutions of 9-benzyl-6-chloro-7,8-dihydropurine and 6-chloro-9-trityl-7,8-dihydropurine turned out to be prone to spontaneous oxidation to the corresponding purines in the presence of air. Since the 7,8-dihydropurines bearing electron-withdrawing substituents at the 2-, 6-, or 8-positions were reported to be more stable to oxidation, 12 we envisioned that the introduction of an electron-withdrawing group to the N 9 -position of 7,8-dihydropurines could lower the electron density and thus increase the overall stability of 7,8-dihydropurines to the oxidation as well.…”
mentioning
confidence: 99%
“…Thus, dihydropurines 2a,b can be obtained accordingly in 92% isolated yield in two steps starting from 6chloro or 6-iodopurine. Since the previous study 11 revealed that the reactivity of 6-iodopurines was very similar to that of 6-chloro derivatives, the easier accessible 6chloro derivative 2a was used in the reactions mentioned here. 14 The ability of 2a to undergo spontaneous oxidation in solution was also tested.…”
mentioning
confidence: 99%